2011
DOI: 10.1088/0031-9155/56/19/016
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave–bubble interaction near soft and rigid boundaries during lithotripsy: numerical analysis by the improved ghost fluid method

Abstract: Abstract. In the case of extracorporeal shock wave lithotripsy (ESWL), a shock wave-bubble interaction inevitably occurs near the focusing point of stones, resulting in stone fragmentation and subsequent tissue damage. Because shock wave-bubble interactions are high-speed phenomena occurring in the tissue consisting of various media with different acoustic impedance values, numerical analysis is an effective method for elucidating the mechanism of these interactions. However, the mechanism has not been examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 39 publications
2
38
1
1
Order By: Relevance
“…For the distal vessel wall, the fitting parameters are given by A = 2.25, B = 1.05 and C = −0.80, while those for the proximal vessel wall are given by A = 0.66, B = 1.36 and C = −1.17. Note that the power law is typically used to correctly model the relationship between the maximum pressure experienced at a rigid planar wall and the distance of the latter away from a bubble at collapse [3, 4, 18, 22]. It fits the pressure data well, however, despite the compliance and displacement of the distal and proximal vessel walls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the distal vessel wall, the fitting parameters are given by A = 2.25, B = 1.05 and C = −0.80, while those for the proximal vessel wall are given by A = 0.66, B = 1.36 and C = −1.17. Note that the power law is typically used to correctly model the relationship between the maximum pressure experienced at a rigid planar wall and the distance of the latter away from a bubble at collapse [3, 4, 18, 22]. It fits the pressure data well, however, despite the compliance and displacement of the distal and proximal vessel walls.…”
Section: Resultsmentioning
confidence: 99%
“…[17] and Kobayashi et al . [18], but in the context of the shock-induced collapse of a bubble near a soft tissue simulant. Freund et al .…”
Section: Introductionmentioning
confidence: 99%
“…Kidney stones — particularly those located in the collecting system of the kidney — are often immersed in a volume of urine, which contains bubbles. Both experimental and computational studies have shown that bubbles in the focal region of LSW may collapse violently when the compressive shock front passes by, generating another shock wave, which propagates into the stone . The time scale of bubble collapse is of the order of 0.1 μ s. Therefore, this shock wave resulting from bubble collapse interacts with the LSW both inside and outside the stone.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, contrary to its aim, shockwave cleaning would increase patients discomfort, logistic and financial expenditure. Nevertheless, shockwave technology will be further developed and its effects on stones and tissue investigated using new techniques [45][46][47]. The resulting modifications of shockwave focusing, coupling, application, pulse repetition rate or intensity might improve the cleansing effect on PBE, which then should be evaluated again.…”
Section: Discussionmentioning
confidence: 99%